Trends in biotechnology: Vibrio natriegens as potential micro-factory for valorization of crustacean waste - Nguyen, Thanh Hung; Tran, Thi Van Anh; Dam, Thuy-Hang; Pham, Tuan-Anh; Le, Thanh Ha; Le, Tuan (Academia Journal of Biology, 2024)
Vibrio natriegens has recently been identified as a promising host for the biotechnology industry thanks to its inherent qualities, which include its fast growth rate, non-pathogenicity to humans, and versatility in using substrates. These advantages have led to the potential use of V. natriegens in the biosynthesis of several products. Basically, the industrial scale requires fermentation or cultivation processes to be conducted at high substrate or biomass concentrations to maximize the final retrieved product. However, studies on V. natriegens at high cell density are limited. Besides, the potential of V. natriegens to convert recalcitrant substrates such as chitin derivatives into biological products has not yet been understood. This review summarizes up-to-date information on the physiological characteristics, metabolism, genome, and genetic modification tools of V. natriegens. Subsequentially, statistics and analysis of research trends related to V. natriegens was presented. Finally, a discussion on the role of V. natriegens in converting chitin waste from the seafood processing industry into a culturing feedstock to achieve a circular economy and net zero emissions was provided.